Model Kesetimbangan Pada Adsorpsi Ion Kadmium (Cd2+) Menggunakan Hidroksiapatit Dengan Variasi Konsentrasi Cd2+ Dan Dosis Adsorben - Fifiyana, Rahma; Fadli, Ahmad; Drastinawati, Drastinawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Release of ion Cadmium (Cd2+) onto water as result of industrial activities and its waste stream causes a negative impact for environment and human health. One of method that used for heavy metal removal is adsorption process. The purpose of this research was to adsorb ion Cd2+ by Hydroxyapatite (HAp) with initial concentration and adsorbent dosage variations then determine the appropriate using Langmuir, Freundlich and DKR isotherm models. In this research, the adsorption behavior of hydroxyapatite with respect to Cd2+ has been studied in order consider its application to purity metal finishing wastewater. Surface area of HAp obtained from the BET method was 6,68 m2/g. The batch adsorption method has been employed, using metal concentration in solution ranging from 20 to 40 mg/L. And dosage adsorbent ranging from 1 to 2 g/L. Cd2+ concentration in the solution was analyzed using AAS. The Langmuir, Freundlich and Dubinin- Kaganer- Radushkevich (DKR) isotherms applied in this study. The adsorption data follow the adsorption equilibrium described well by the DKR isotherm model with adsorption energy value (E) ranging from 8,45-11,18 kJ/mol. It was explained that ion exchange described as mechanism for adsorption of Cd2+ onto HAp.Keywords: adsorption, cadmium (Cd), equilibrium model, hydroxyapatite